Spatial Index Modulation With the Combination of Both Antenna Indexes and Two Constellations - Ping Yu; Fuchun Huang (IEEE Access, 2022)
In this paper, in order to further exploit the antenna index (AI) domain for increasing the spectral efficiency, we propose a new schematic of enhanced generalized spatial modulation with both three dimension constellation and QAM constellation (EGSM-3DQ) to enhance the active AI combinations with the construction of three dimension (3D) signal constellation. In the EGSM-3DQ, a transmit vector symbol (TVS) consists of two spatial vector symbols (SVS) with the aid of one vector index bit, one SVS of which is obtained by modulating three components of a 3D signal symbol on two or three active transmit antennas (TAs) through the 3D Signal Mapper and AI Vector Modulator, another SVS of which is obtained by modulating one or multiple mapped QAM symbols on one or multiple active TAs through the AI Vector Selector. In addition, by jointing the AIes and multiple constellations such as the 3D and QAM, PAM constellations, grouping EGSM (gEGSM) is proposed to develop the group index combinations to increase extra index information. Finally, the comparisons of squared minimum Euclidean distances (MED) and the average bit error probability are provided. Simulation results show that the proposed schemes improve the bit error rate performance as compared with conventional systems.